Nexus Islamic Finance Development and Income Inequality in Indonesia: Testing Kuznets Curve Hypothesis - Shofi Dana, Badara; Himmati, Risdiana; Salim, Agus (Economica: Jurnal Ekonomi Islam, 2025)
This study analyzes the applicability of the Kuznets curve hypothesis within the specific context of Islamic finance development in Indonesia and its resultant implications for income inequality. The novelty of this research lies in integrating Islamic finance, specifically from the banking sector, with Islamic social finance instruments, namely zakat, infaq, and sadaqah. Crucially, it interrogates whether the Kuznets curve hypothesis remains pertinent within this expanded framework. Utilizing secondary panel data encompassing 25 Indonesian provinces over the 2019–2020 period, the study employs panel data regression techniques, specifically common effect, fixed effect, and random effect models, which were systematically selected via the Chow, Hausman, and Lagrange multiplier tests. The empirical findings demonstrate unequivocally that the development of Islamic finance, spanning both the financial and social sectors, significantly influences income inequality. This substantiates the Kuznets curve hypothesis: inequality initially escalates but subsequently diminishes as development matures. Furthermore, the results underscore the role of the Human Development Index (HDI) and the prevalence of mosques in mitigating inequality, while population density exhibits a positive association with inequality. This study conclusively argues that strengthening financial inclusion and professionalizing the management of Islamic social finance constitute strategic approaches for mitigating income inequality in Indonesia.